Flux expansion effect on turbulent transport in 3D global simulations. (August 2017) - Galassi, D.; Tamain, P.; Baudoin, C.; Bufferand, H.; Ciraolo, G.; Fedorczak, N.; Ghendrih, Ph.; Nace, N.; Serre, E.
Highlights: TOKAM3X simulations are run with three geometries with different Shafranov shifts. Turbulent cross-field fluxes normalized by flux expansion are similar in the three cases. Steeper density gradients are found when flux surfaces are compressed at LFS. Larger security factor at LFS leads to larger parallel extension of unstable region. Increasing magnetic shear improves turbulence stabilization. Abstract: The flux expansion effect on the Scrape-Off Layer equilibrium is inspected through TOKAM3X 3D turbulence simulations. Three magnetic equilibria with analytically controlled flux expansion are built, representing respectively a positive, a null and a negative Shafranov shift. Turbulent E × B fluxes across flux surfaces show similar amplitudes and poloidal distributions in all cases. The ballooning nature of the interchange instability is recovered, with an enhancement of turbulence in the vicinity of the limiter, probably due to a Kelvin–Helmoltz instability. Interestingly, the poloidally averaged density decay length is found to be shorter almost by a factor 2 in the case of flux surfaces compressed at the low-field side midplane, with respect to the opposite case, indicating the presence of unfavorable conditions for the turbulent transport. The difference in the magnetic field line shape is pointed out as a mechanism which affects the turbulent transport across the flux surfaces. Indeed the unstable region has a larger parallel extension when flux expansion in the low-field side is larger. Moreover, the configuration with a lower magnetic shear at the low-field side midplane shows a more unstable behavior. The role of this parameter in turbulence stabilization is qualitatively evaluated. The difference in the distribution of transport along the parallel direction is shown to affect also the parallel flows, which are analyzed for the three proposed cases.